2011
DOI: 10.1158/0008-5472.can-10-2745
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen Receptor Induces Integrin α6β1 to Promote Prostate Tumor Cell Survival via NF-κB and Bcl-xL Independently of PI3K Signaling

Abstract: Recent studies indicate that androgen receptor (AR) signaling is critical for prostate cancer cell survival, even in castration-resistant disease wherein AR continues to function independently of exogenous androgens. Integrin-mediated adhesion to the extracellular matrix is also important for prostate cell survival. AR-positive prostate cancer cells express primarily integrin a6b1 and adhere to a laminin-rich matrix. In this study, we show that active nuclear-localized AR protects prostate cancer cells from de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 50 publications
7
65
0
Order By: Relevance
“…Since AR signaling suppresses the expression of β4, c-Met, and ErbB2 (84, 85), androgen withdrawal experiments have suggested that focal adhesion kinase, which is activated by multiple β1 integrins, promotes the expansion of tumor progenitor cells in mouse models of mammary and intestinal tumorigenesis (73)(74)(75). Finally, although not directly focusing on tumor progenitor cells, prior studies have emphasized a role for β1 integrins, but not for β4, in prostate cancer (37,(76)(77)(78)(79). Our observation that β4 signaling is dispensable for prostate development but not tumorigenesis is consistent with the hypothesis that tumor cells are exquisitely dependent on certain integrin signaling pathways, such as those activated by β4, whereas their normal counterpart are not (32,74).…”
Section: Figurementioning
confidence: 99%
“…Since AR signaling suppresses the expression of β4, c-Met, and ErbB2 (84, 85), androgen withdrawal experiments have suggested that focal adhesion kinase, which is activated by multiple β1 integrins, promotes the expansion of tumor progenitor cells in mouse models of mammary and intestinal tumorigenesis (73)(74)(75). Finally, although not directly focusing on tumor progenitor cells, prior studies have emphasized a role for β1 integrins, but not for β4, in prostate cancer (37,(76)(77)(78)(79). Our observation that β4 signaling is dispensable for prostate development but not tumorigenesis is consistent with the hypothesis that tumor cells are exquisitely dependent on certain integrin signaling pathways, such as those activated by β4, whereas their normal counterpart are not (32,74).…”
Section: Figurementioning
confidence: 99%
“…Whether a pharmacological strategy would result in such pathologies occurring during development is uncertain but will need to be tested. Future studies might also highlight a potential net benefit of targeting other cellular pools of this integrin, since some of them, notably those expressed on endothelial or tumor cells, also actively participate in cancer progression (22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α6β1, which is expressed on cancer and endothelial cells, has been described to favor tumor angiogenesis, invasiveness, and cancer progression (22)(23)(24)(25)(26)(27). Besides laminins, this integrin has also been reported to bind ADAM9/meltrin-γ, a member of the a disintegrin and metalloproteinase (ADAM) family of proteins (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…There was a greater loss of adhesion in LNCaP than in C4-2 cells. Cell adhesion to matrix is required for cell survival of most epithelial cells, including in prostate and prostate cancer cells (8,9). To determine if the cells were dying, both adherent and non-adherent cells were collected and stained with Trypan Blue.…”
Section: Summary Of Aimmentioning
confidence: 99%